2007
DOI: 10.1213/01.ane.0000261277.65343.4e
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Chromosome 7 Harbors a Quantitative Trait Locus for Isoflurane Minimum Alveolar Concentration

Abstract: Both methods of genetic analysis identified a QTL for isoflurane MAC that was located on the proximal part of mouse chromosome 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The rectal temperature was periodically checked to ensure maintenance of normothermia (Fisher Scientific, Pittsburgh, PA) at 37±0.5°C. The level of exposure for sevoflurane was determined after calculating the minimum alveolar concentration (MAC) equivalent to isoflurane 18-20. The 0.75% isoflurane or 1.1% sevoflurane is about equipotent to ~0.5 MAC in mice.…”
Section: Methodsmentioning
confidence: 99%
“…The rectal temperature was periodically checked to ensure maintenance of normothermia (Fisher Scientific, Pittsburgh, PA) at 37±0.5°C. The level of exposure for sevoflurane was determined after calculating the minimum alveolar concentration (MAC) equivalent to isoflurane 18-20. The 0.75% isoflurane or 1.1% sevoflurane is about equipotent to ~0.5 MAC in mice.…”
Section: Methodsmentioning
confidence: 99%
“…Individual mongrel cats show differential sensitivity to modern VGAs 8 as do segregated human populations for SEVO 9 11 . These data raise the possibility that anesthetic sensitivity may behave like a quantitative trait 12 , 13 , as opposed to being mediated by a small number of discrete molecular targets. By contrast, Mendelian mutations have pronounced effects on the sensitivity to VGAs in model organisms 14 16 and can result in life-threatening consequences 17 , 18 .…”
Section: Introductionmentioning
confidence: 98%
“…Champy et al [ 57 ] reported that circulating total cholesterol levels were significantly higher in unanesthetized male C57BL/6J mice when compared to isoflurane anesthetized counterparts. Since inbred strains of mice differ in their sensitivity for isoflurane and a QTL for this phenotype has been described [ 87 ], it can be argued that the use of anesthesia influence the chromosomal assignment of QTLs for baseline circulating total cholesterol level in mice.…”
Section: Resultsmentioning
confidence: 99%